Cover Feature: Dimensioning the Term Carbenoid (Chem. Eur. J. 58/2017). Issue 58 (22nd August 2017) - Caballero, Ana; Pérez, Pedro J.
Abstract : In the context of metal‐induced diazo decomposition, carbenoids are intermediates en route to metal–carbene complexes, in which the ambiguous use of carbenoids and metal–carbenes for the same species is not appropriate. The picture shows the Muelle Minero at Port of Huelva (Spain), where copper ore (one of the metals employed for carbene‐transfer reactions) was exported to Europe for nearly two centuries. More information can be found in the Concept article by A. Caballero and P. J. Pérez onpage 14389 .